Cultural Records shown by the songs of Perunkadungo - S, Selvakumar (International Research Journal of Tamil, 2022)
Culture is capable of giving humanity greatness, welfare, and specific identities. Cultural elements take the lead in the construction of individual superiority and social improvements. Literature plays a significant role in the factors that reveal the cultural environment of a society. In this way, the Sangam literary texts are of great help in understanding the cultural milieu of the Sangam era. The great poets of the Sangam age recorded in their poems the cultural aspects of the people who lived at that time. The cultures of the Sangam era can be called the Thinai culture and the Ainthinai culture. Perunkadungo is one of the great poets of the Sangam age. He belonged to Kongu Nadu, one of the ancient kingdoms of Tamil Nadu. He is good at singing Paalai Thinai songs. Therefore, he is called Perunkadugo, who sang paalai. He has revealed the cultural aspects of the period through the Agathinai people in his songs. The purpose of this paper is to project them.